The salon culture in the XVII century and the english heroic romance - Kuznetsova Alena (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
In the article the salon culture is regarded. The salon culture was brought from France into England fi rst in the suite of Henrietta Maria in 1625 and later by the English courtiers, who fl ed to the continent during the Civil War. However, in contrast to France, where members of the salons were themselves authors of romances, English writers focused not on the activity of the domestic préciosités, but on that of the French salons.